Combination of sorption properties of polydimethylsiloxane and solid‐phase extraction sorbents in a single composite material for the passive sampling of polar and apolar pesticides in water. Issue 20 (22nd September 2016) - Martin, Alexis; Margoum, Christelle; Coquery, Marina; Randon, Jérôme
Abstract : Passive sampling techniques have been developed as an alternative method for in situ integrative monitoring of trace levels of neutral pesticides in environmental waters. The objective of this work was to develop a new receiving phase for pesticides with a wide range of polarities in a single step. We describe the development of three new composite silicone rubbers, combining polydimethylsiloxane mechanical and sorption properties with solid‐phase extraction sorbents, prepared as a receiving phase for passive sampling. A composite silicone rubber composed of polydimethylsiloxane/poly(divinylbenzene‐co‐ N ‐vinylpyrrolidone) was selected by batch experiments for its high sorption properties for pesticides with octanol‐water partition coefficients ranging from 2.3 to 5.5. We named this composite material "Polar/Apolar Composite Silicone Rubber". A structural study by scanning electron microscopy confirmed the homogeneous dispersion of the sorbent particles and the encapsulation of particles within the polydimethylsiloxane matrix. We also demonstrate that this composite material is resistant to common solvents used for the back‐extraction of analytes and has a maximal resistance temperature of 350°C. Therefore, the characteristics of the "Polar/Apolar Composite Silicone Rubber" meet most of the criteria for use as a receiving phase for the passive sampling of pesticides.